2012
DOI: 10.1155/2012/594986
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and Inflammation

Abstract: Factor V Leiden, is a variant of human factor V (FV), also known as proaccelerin, which leads to a hypercoagulable state. Along these years, factor V Leiden (FVL) has been studied from the pathophysiologic point of view, and research has been focused on finding clinical approaches for the management of the FVL associated to a trombophilic state. Less attention has been paid about the possible role of FVL in inflammatory conditions known to be present in different disorders such as uremia, cirrhosis, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
(108 reference statements)
1
9
1
1
Order By: Relevance
“…The role of Factor V Leiden @@is important in chronic inflammation and this condition may have a role in the hepatic fibrogenesis, throughout the activation of stellate cells (Perez-Pujol et al, 2012); this THRGF was not significantly correlated to any clinical variable, in the present study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The role of Factor V Leiden @@is important in chronic inflammation and this condition may have a role in the hepatic fibrogenesis, throughout the activation of stellate cells (Perez-Pujol et al, 2012); this THRGF was not significantly correlated to any clinical variable, in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…The role of hypercoagulability in the liver fibrogenesis is well known, and many authors are studying this argument for many years (Adinolfi et al, 2005;Toniutto et al, 2008;Assy et al, 2005;Anstee et al, 2011;Perez-Pujol et al, 2012;Maharshak et al, 2011). PAI-1 has an active role in liver fibrosis in rats (Zhang et al 1999), through a pathogenic mechanism leading to the stellate cell activation, today considered the key of liver fibrogenesis (AbdulHameed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been suggested that the inflammatory response may further increase the thrombotic risk in FVL patients. Damage of the endothelium as well as exposure of adhesion molecules may play a major role in upregulating the thrombophilic state in this group of patients [30]. Last but not least, the risk of PE is only mildly elavated in FVL carriers.…”
Section: Discussionmentioning
confidence: 99%
“…El factor V de la coagulación (FV), proacelerina o factor lábil, es sintetizado en el hígado, no es activo enzimáticamente, circula por el plasma libre como una cadena polipeptídica simple en una forma procoagulante inactiva y actúa como cofactor de la APC en la inactivación del factor VIIIa (36)(37)(38). El gen que codifica para el FV se encuentra en el brazo largo del cromosoma 1 (1q23).…”
Section: Factor Vunclassified